Mujeres como territorio de despojo: extractivismo, femicidios y violencia de género en el norte de Chile - Ibacache-Corante, Andrea (2024)
This text explores different socio-historical and theoretical contents that shape the current experiences of women who live in the territories of what is known today as the north of Chile. The objective is to contribute to the theoretical approach in the analysis of social and gender inequalities in a context marked by mining extractivism and the vulnerability of its inhabitants. From a gender perspective, we analyze extractivism in the area and its consequences beyond environmental issues. The main conclusion is that the intersection of the issues addressed requires complex analyses where they can converge to strengthen the fusion of issues with a denouncing and innovative perspective.